Sexual dysfunction among people with mental illness attending follow-up treatment at a tertiary hospital, Jimma University Medical Center: A cross-sectional study - Sewalem, Jerusalem; Kassaw, Chalachew; Anbesaw, Tamrat (Frontiers in Psychiatry, 2022)
Abstract Background: Sexual function is a complex behavior influenced by several factors that result in dysfunction. It is highly prevalent among patients with mental illness who are on psychotropic medications. Assessing those patients has paramount importance for appropriate intervention to take place. Methods: This study was Facility based cross-sectional study design conducted in June 2022. A Sexual Functioning Questionnaire (CSFQ-14) was used to assess sexual dysfunctions. Data were analyzed using SPSS version 21 software. Logistic regression analysis was performed to assess the association between dependent and independent variables. In-dependent Variables with a p-value < 0.05 were taken as statistically significant with sexual dysfunction. Result: The prevalence of sexual dysfunction was 45.4 % among respondents. The presence of chronic medical illness, being on typical antipsychotic treatment, being on psychiatric treatment for 24 months and an above, moderate level of alcohol use, and age above 35 years and above were significantly associated with sexual dysfunction. Conclusions: The prevalence of sexual dysfunction among people with mental illness is high. Therefore, the clinician needs to routinely enquire about sexual symptoms during follow-up treatment and give appropriate interventions with special attention to patients with chronic medical conditions and patients taking antipsychotics and psychotropic drugs for a long period of time.